2001
DOI: 10.1128/jcm.39.11.4145-4148.2001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Quantitative PCR To Measure Density of Borrelia burgdorferi in the Midgut and Salivary Glands of Feeding Tick Vectors

Abstract: Quantitative real-time PCR was used to assay spirochetes in feeding ticks. Spirochetes in tick midguts increased sixfold, from 998 per tick before attachment to 5,884 at 48 h of attachment. Spirochetes in tick salivary glands increased >17-fold, from 1.2 per salivary gland pair before feeding to 20.8 at 72 h postattachment. The period of the most rapid increase in the number of spirochetes in the salivary glands occurred from 48 to 60 h postattachment; this time period coincides with the maximal increase in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 20 publications
6
133
1
1
Order By: Relevance
“…The complemented strain (BbDTR653) also regained the ability to sustain spirochetal numbers through the molting process (P Ď˝ 0.044), albeit not quite to wild-type levels ( Table 2). Of note, levels of wild-type PL133 dropped normally (40) in fed larvae during the 4-to 5-week time frame between larval tick engorgement and metamorphosis to the nymphal form (Fig. 2), whereas the bptA deficiency resulted in an accelerated loss of spirochetes within the first 2 weeks postrepletion ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The complemented strain (BbDTR653) also regained the ability to sustain spirochetal numbers through the molting process (P Ď˝ 0.044), albeit not quite to wild-type levels ( Table 2). Of note, levels of wild-type PL133 dropped normally (40) in fed larvae during the 4-to 5-week time frame between larval tick engorgement and metamorphosis to the nymphal form (Fig. 2), whereas the bptA deficiency resulted in an accelerated loss of spirochetes within the first 2 weeks postrepletion ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the notion that needle exposure by no means reflects the situation of tick infection [23,25,54] and the highly improved real-time PCR technique to quantify B. burgdorferi in situ [24,27,43,46,48,62,63,64], we have now performed a detailed quantitative analysis of the spirochete burden and population dynamics in different tissues of mice following natural (tick) infection by B. burgdorferi s.s. (ZS7) for a period of 4 months postinfection (p.i.). For this purpose we have selected one cp26-encoded gene, ospC [40], and four previously described lp54-encoded genes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(25) and others (26) have demonstrated that borrelial shuttle vectors can be lost over time in the absence of selection during in vivo growth. We reasoned that insertion of a gfp expression cassette into cp26, a highly stable, endogenous borrelial plasmid (27,28), would prevent loss of the fluorescent reporter during the extensive replication of spirochetes that occurs following the nymphal blood meal (14,29), thereby enhancing our ability to track organisms in locales where bacterial burdens are known to be low (e.g., hemolymph and salivary glands) (15,18,30,31). To this end, Bb914 was generated by inserting gfp under the control of the constitutive flaB promoter (P flaB -gfp) into the bbb20-bbb21 intergenic region of cp26 in CE162, a virulent B. burgdorferi 297 clone (32) (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/ JCI39401DS1).…”
Section: Introductionmentioning
confidence: 99%